MONITORING OF MORPHOLOGICAL EFFECTS AUTOLOGICAL MESENCHIMAL STEM CELLS, TRANSPLANTED IN LIVER WITH VIRUS CYRROSIS (clinical observation) - S. P. Lukashyk; O. V. Aleinikova; V. M. Tsyrkunov; Y. I. Isaikina; R. I. Кravchuk (Архивъ внутренней медицины)
Introduction. The importance of the HCV-infection is determined by the wide spread, progressive course, the formation of liver cirrhosis (LC) and hepatocellular carcinoma. The mechanisms of the effect of the virus on hepatic cells, the processes of fibrogenesis and fibrolysis, mechanisms of the reverse development of the LC remain unexplored. There is no effective pathogenetic therapy. The aim of the study — determination of the effectiveness and safety of intrahepatic transplantation of mesenchymal stem cells (MSC) in chronic HCV-infection at the stage оf LC. Methods. A patient with HCV-LC who has a secondary hemorrhagic vaculities who underwent autologous MSC transplantation into the liver tissue. The liver biopsy specimens were studied in dynamics by light and electronic microscopy and by immunohistochemistry. Results. The transplantation and posttransplantation period proceeded without complications. After the introduction of MSC the features of the formed micronodular LC remained. In some parts of the samples, the septa looked thin, sometimes perforated, indicating a resorption in this place of fibrous tissue. There was a decrease in the degree of transdifferentiation of stellate cells into myofibroblasts, a decrease in the number of fibroblasts and fibroblasts, there were no immune reactions in the form of deposition of amorphous and fibrous masses of moderate electron density along the sinusoidal capillaries that were significantly expressed in the primary biopsy. These changes were combined with the appearance of hepatocyte heterogeneity in the density of the cytoplasmic matrix, the state and quantity of organelles and inclusions, and the structural improvement of intracellular organelles. Conclusion. Autologous transplantation of mesenchymal bone marrow stem cells reduces the degree of destructive changes in hepatocytes, the severity of fibrosis and contributes to the improvement of the morpho-functional state of the liver, and therefore, it can be recommended as an important component of medical interventions.